Emerging perspectives on the design, use, and evaluation of mobile and handheld devices - Lumsden, Joanna (Advances in wireless technologies and telecommunication (AWTT) book series., 2015)
"This book is an authoritative reference source consisting of the latest scholarly research and theories from international experts and professionals on the topic of human-computer interaction with mobile devices"--